A highly efficient concurrent dual‐band GaN class‐AB power amplifier at 1.84 GHz and 3.5 GHz. Issue 9 (16th July 2017) - Rezaei Borjlu, Shaban; Asemani, Davud; Dousti, Massoud
Abstract: This article presents the design, simulation, implementation, and experimental results of a highly efficient, concurrent dual‐band, gallium nitride (GaN), class‐AB power amplifier (PA) at two frequencies: 1.84 and 3.5 GHz. It proposes a novel dual‐band bandpass filter (DBBPF) with quad‐section stepped‐impedance resonators (SIRs) capable of rejecting the annoying frequencies of the second and third harmonics in the dual‐band. The proposed DBBPF was applied in the design of a dual‐band PA using a packaged 10 W GaN transistor. The PA prototype maintained a peak power‐added efficiency (PAE) of 75.3% at the 1.84 GHz frequency and 64.5% at the 3.5 GHz frequency. For a continuous wave output power of 40.9 dBm, the measured gain was 13 dB in the two frequency bands. Linearized modulated measurements, concurrently using 10 MHz quadrature amplitude modulation (16 QAM) signals and worldwide interoperability for microwave access (WiMAX) signals, showed an average PAE of 48.5% and 39.8% and an adjacent channel leakage ratio of −46 and −45 dBc with an average output power of 37.8 and 36.8 dBm at the two frequency bands, respectively. This PA is used for wireless systems. It is especially useful in standard simultaneous global system for mobile (GSM) and WiMAX wireless systems.